MALEFICENT’S SUPEREGO IN ROBERT STROMBERG’S “MALEFICENT” MOVIE (2014) - Werdarini, Ana Hening Kusuma; Triwijayanti, Adinda Zahra; Rahmatika, Nadia; Nabila, Salsa (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
This research is conducted to describe Maleficent’s superego and its function in Robert Stromberg’s Maleficent movie 2014 version by applying Sigmund Freud’s psychoanalysis. The qualitative method is used to describe the analysis. The result of this research reveals the evolution of Maleficent’s superego before and after Aurora’s birth. The first one is the superego believing that humans are wicked, represented by the human king and Stefan. In the second one, after meeting Aurora, her superego changes into believing that humans can be good. In the end, she is the true love of Aurora and can live side by side with her, eventually leading a harmonious life with the human kingdom. Hence, the superego’s function in the movie is pivotal to the plot twist, redefining Maleficent as both a villain and a heroine.